Building Effective Leadership Change in Organisations - Putri, Saidina (Jurnal Pusat Manajemen, 2024)
Leadership is a management concept in an organization that has a social position that will be indispensable in group activities. Leadership also serves as the main principle of organizing and driving all processes in the organization. The writing of this article aims to understand how to build effective leadership changes in the organization and accompanied by Islamic elements in it. The method of writing this article is to use a qualitative method which is sourced from several journals and books related to the issues discussed. The result of this article is that effective leadership in an organization is characterized by a leader who must have wisdom and responsibility in carrying out his duties so as to achieve the desired goals. A leader must also be a reflection with a good attitude in order to be an example of his employees, because a quality organization we can see from the way of leadership.